2019
DOI: 10.1039/c9ra02095k
|View full text |Cite
|
Sign up to set email alerts
|

Oxidatively induced exposure of active surface area during microwave assisted formation of Pt3Co nanoparticles for oxygen reduction reaction

Abstract: The oxygen reduction reaction (ORR) is efficiently facilitated platinum catalysts alloyed with Co and reveal high electrochemically active surface area via rapid microwave synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…For this process, we selected the 1:1 composition because this is the only mixture capable of forming a fully ordered L1 0 phase, specially aided by a reductive atmosphere (H 2 ). 20,26−29 The FePt(1:1) samples possessed a near 1:1 composition and without residual traces from the NH 4 NO 3 oxidant (see X-ray photoelectron spectra in Supporting Information Figure S3), similarly observed for Pt 3 Co. 18 Previously reported solid-state synthesis methods have shown that the metal ratio in the bulk samples corresponds well with the initial precursor composition. 15,18,19 Figure 2a shows the XRD patterns of the catalysts and display typical Pt/Pt-alloy reflections [i.e., Pt(111), Pt(200), and Pt(220)], 30,31 but notably, Fe-oxide features [between Pt(111) and Pt(200), see Supporting Information Figure S4] emerge only for samples with the highest Fe content, indicating that the majority of Fe is well intermixed into the Pt fcc lattice.…”
Section: Resultsmentioning
confidence: 63%
See 3 more Smart Citations
“…For this process, we selected the 1:1 composition because this is the only mixture capable of forming a fully ordered L1 0 phase, specially aided by a reductive atmosphere (H 2 ). 20,26−29 The FePt(1:1) samples possessed a near 1:1 composition and without residual traces from the NH 4 NO 3 oxidant (see X-ray photoelectron spectra in Supporting Information Figure S3), similarly observed for Pt 3 Co. 18 Previously reported solid-state synthesis methods have shown that the metal ratio in the bulk samples corresponds well with the initial precursor composition. 15,18,19 Figure 2a shows the XRD patterns of the catalysts and display typical Pt/Pt-alloy reflections [i.e., Pt(111), Pt(200), and Pt(220)], 30,31 but notably, Fe-oxide features [between Pt(111) and Pt(200), see Supporting Information Figure S4] emerge only for samples with the highest Fe content, indicating that the majority of Fe is well intermixed into the Pt fcc lattice.…”
Section: Resultsmentioning
confidence: 63%
“…20,26−29 The FePt(1:1) samples possessed a near 1:1 composition and without residual traces from the NH 4 NO 3 oxidant (see X-ray photoelectron spectra in Supporting Information Figure S3), similarly observed for Pt 3 Co. 18 Previously reported solid-state synthesis methods have shown that the metal ratio in the bulk samples corresponds well with the initial precursor composition. 15,18,19 Figure 2a shows the XRD patterns of the catalysts and display typical Pt/Pt-alloy reflections [i.e., Pt(111), Pt(200), and Pt(220)], 30,31 but notably, Fe-oxide features [between Pt(111) and Pt(200), see Supporting Information Figure S4] emerge only for samples with the highest Fe content, indicating that the majority of Fe is well intermixed into the Pt fcc lattice. Interestingly, reflections corresponding to the superlattice fct structure [broad (110) peak] become more pronounced for samples with X = 1,2,3 (FePt(X:1)/C*), implying that MW treatment forms NPs under high temperatures.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…In addition, carbon nanomaterials act as excellent material support by facilitating the production of nanoparticulate structures, minimizing agglomeration, improving stability, and enhancing electron transport. [20][21][22][23] We, therefore, exploit the ability of nanocarbons to easily absorb microwaves to develop a solid-state synthesis process driven by microwave irradiation to produce cobalt-doped edgeterminated layered MoS 2 directly on nitrogen-doped reduce graphene oxide (N-rGO x ). The as-produced Co-MoS 2 exhibited the CoMoS phase, and only a slight segregation to cobalt suldes was observed at Co content above 15 at%.…”
Section: Introductionmentioning
confidence: 99%